2019
DOI: 10.3390/su11164280
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Economic, Demographic, and Weather Factors on the Exit of Beginning Farmers in the United States

Abstract: The success of efforts to promote sustainability and growth of Beginning Farmers and Ranchers (BFRs) depends on a set of diverse factors whose individual impacts on the BFR survival in or exit from farming need further clarification. This paper evaluates how a variety of economic and demographic factors, together with weather variability, affect BFRs' exit from farming using farm-level data from the US Census of Agriculture for the period 1992-2012. The analysis uses insights from the literature on firm exit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 33 publications
0
24
1
Order By: Relevance
“…Although explaining people’s career decisions needed to incorporate as many relevant factors as possible, among these factors, income is one of the most important factors to explaining career decisions. Gross farming income (sales volume) was included as an explanatory variable in the analysis of Nadolnyak et al [ 23 ], which showed gross income had a negative impact on young farmers’ decisions to exit farming. Farming income also varies with off-farm income, farm type (i.e., small-scale and subsistence farming, lifestyle farming), farm size and farming revenues, farm activity (e.g., livestock, cash crops, staple food), farm location, farm diversification, farmers’ age, farming experience, and government payments [ 24 ].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Although explaining people’s career decisions needed to incorporate as many relevant factors as possible, among these factors, income is one of the most important factors to explaining career decisions. Gross farming income (sales volume) was included as an explanatory variable in the analysis of Nadolnyak et al [ 23 ], which showed gross income had a negative impact on young farmers’ decisions to exit farming. Farming income also varies with off-farm income, farm type (i.e., small-scale and subsistence farming, lifestyle farming), farm size and farming revenues, farm activity (e.g., livestock, cash crops, staple food), farm location, farm diversification, farmers’ age, farming experience, and government payments [ 24 ].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Individual factors–age, formal education, skills and abilities, gender, and race [ 12 , 22 , 23 , 26 , 28 , 30 ],…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Access to credit is also important in the context of the pending transition of farm assets from retiring operators to the new generations of farmers, as well as in the context of the agricultural downturn and the economic consequences of the COVID-19 pandemic [15][16][17][18]. For example, BFRs are at a greater risk of financial stress and the agricultural downturn has negatively affected their profitability, liquidity, and solvency, although it had no effect on their repayment capacity [19].…”
Section: Introductionmentioning
confidence: 99%